The Use of Snowball Throwing Learning Model to Improve Students’ Civics Learning Outcomes in the Topic of “The Freedom to Join Organizations” - Toni Nasution; Winda Simanjuntak (Jurnal Basicedu, 2023)
Improving learning outcomes is a concrete form of learning evaluation and improving the quality of the learning process, so that learning necessitates this quality improvement. This study aims to describe efforts to improve student learning outcomes by using the snowball throw learning model in civics subjects on freedom of association. To find systematic (scientific) results, the researcher used a classroom action research approach with three stages, namely pre-action, first cycle, and second cycle. The background of this research took place at SD Negeri 108307 Pasar VIII, Buntu Bedimbar Village, with a total of 19 students (grade V). The results of this study concluded that the snowball throw learning model had a positive or significant impact on improving student learning outcomes. Pre-action results showed that 4 students achieved the minimum completeness criteria (KKM) (21.05%) and 15 students had not yet reached the KKM (78.95%). After using the snowball throw learning model, in cycle I there was an increase, where 7 students achieved KKM (36.85%) and 12 students had not reached KKM (63.15%). Furthermore, in cycle II 19 students had reached the KKM (100%). The implications of this study indicate that the snowball throw can help improve student learning outcomes through providing opportunities for cooperative learning or mutual cooperation to understand concepts and solve learning problems.